2012
DOI: 10.3341/kjo.2012.26.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cyclosporine Treatment for Noninfectious Uveitis

Abstract: PurposeTo assess the clinical outcomes of cyclosporine treatment for noninfectious uveitis.MethodsA retrospective review of medical records was completed for 182 noninfectious uveitis patients who were treated with cyclosporine between January 2001 and August 2010. Data was obtained relevant to demographic characteristics, anatomic classification, and laterality of uveitis, associated systemic disorder, dosage of cyclosporine and prednisolone, usage of other immunosuppressive drugs, visual acuity (VA), control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
2
2
Order By: Relevance
“…These data appear to be in contrast to reports by several other authors treating pediatric PP, PU, and VKH with various formulations of steroids and a variety of DMARDs (16,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Expectedly, these studies reported significant degrees of steroid toxicity, including relatively high rates of cataract formation, subretinal neovascularization, and glaucoma requiring cryotherapy, laser photocoagulation, or surgical management (33)(34)(35)(36).…”
Section: Reiff 1594 |contrasting
confidence: 80%
See 1 more Smart Citation
“…These data appear to be in contrast to reports by several other authors treating pediatric PP, PU, and VKH with various formulations of steroids and a variety of DMARDs (16,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Expectedly, these studies reported significant degrees of steroid toxicity, including relatively high rates of cataract formation, subretinal neovascularization, and glaucoma requiring cryotherapy, laser photocoagulation, or surgical management (33)(34)(35)(36).…”
Section: Reiff 1594 |contrasting
confidence: 80%
“…In addition, even though rather mixed results were observed in several studies of DMARDs in patients with PP, PU, and VKH, the results appeared to be better overall when compared to our reported outcomes (39–45). In our study population, MTX was the most commonly used DMARD, prescribed in an average of 92% of patients, followed by MMF in 7.5% of patients, and CSA, which was used in only 1 patient.…”
Section: Discussioncontrasting
confidence: 56%
“…The immunosuppressive effects of cyclosporine occur through reversible inhibition of calcineurin and the prevention of inflammatory function of T cells in the peripheral circulation [ 94 ]. In 1983, cyclosporine was first used for therapy of uveitis by Nussenblatt et al In addition, different research groups have investigated the effects of cyclosporine on serpiginous choroiditis, Behcet’s disease-associated uveitis, VKH disease, birdshot retinochoroiditis and idiopathic uveitis [ 95 ]. In the Systemic Immunosuppressive Therapy for Eye Diseases (SITE) study, cyclosporine monotherapy achieved 33.4% inflammation control at 6 months and 51.9% at 12 months among 373 patients with non-infectious ocular inflammation [ 96 ].…”
Section: Pathogenesis and Experimental Models Of Niumentioning
confidence: 99%
“…[220] As a treatment for patients with uveitis, cyclosporine is effective in controlling inflammation, and its effects are sustained even after the reduction of corticosteroid dosage. [131,221] For example, a retrospective cohort study on 373 patients demonstrated clinically acceptable control over inflammation at 6 months and 1 year for 33.4% and 51.9% of patients, respectively. [222] Despite the efficacy in managing the inflammation, cyclosporine can lead to severe nephrotoxicity, [223,224] and in addition, some patients can be refractory to treatment.…”
Section: Ocular Diseasesmentioning
confidence: 99%